2013
DOI: 10.1179/0267083612z.000000000218
|View full text |Cite
|
Sign up to set email alerts
|

Design of 10Cr martensitic steels for improved creep resistance in power plant applications

Abstract: The drive to increase the efficiency of fossil fired power generation to reduce CO2 emissions and to conserve energy resources has led Tata Steel to design new 10Cr martensitic compositions for use at temperatures of 620°C and above with creep properties superior to steel 92 (9Cr, 0·5Mo, and 2W), which is the best currently available steel of this type. In the new alloys, the chromium content was set at 10 to ensure the required oxidation resistance. The long term creep performance of steels with this level of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
17
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(17 citation statements)
references
References 5 publications
0
17
0
Order By: Relevance
“…Hence a second set of thermodynamic calculations at the service temperature is performed. Three additional go/no-go criteria at this use temperature are enforced: (5) The total amount of non-desirable precipitates, i.e. all precipitates not being MX carbonitrides or Ni3Ti/ NiAl intermetallics should be less than 1 vol.%.…”
Section: Defining the Go/no-go Criteriamentioning
confidence: 99%
See 1 more Smart Citation
“…Hence a second set of thermodynamic calculations at the service temperature is performed. Three additional go/no-go criteria at this use temperature are enforced: (5) The total amount of non-desirable precipitates, i.e. all precipitates not being MX carbonitrides or Ni3Ti/ NiAl intermetallics should be less than 1 vol.%.…”
Section: Defining the Go/no-go Criteriamentioning
confidence: 99%
“…However, the microstructural stability of existing creep steel grades during long term exposure at elevated temperatures is still insufficient. Much effort has been devoted to the development of new martensitic creep-resistant steel with improved creep strength and a decent stability during long term service [2][3][4][5][6][7][8][9][10][11]. Kimura et al's research [12,13] on some ferritic creepresistant steels has shown that at very long times the creep strength reaches a constant value.…”
Section: Introductionmentioning
confidence: 99%
“…As a general realisation of the importance of Z-phase precipitation set in during the following years, observations of Z-phase precipitation in 9-12wt%Cr steels were made by many separate research groups [13][14][15][16]. While the most continuous research has been presented in papers from Danielsen or Sawada, many groups have been involved in more recent characterising of Z-phase precipitation [17][18][19][20][21][22][23][24] as well as atomistic scale modelling [25][26][27][28].…”
Section: Z-phase Backgroundmentioning
confidence: 99%
“…Sachadel et al 3 report the development, aided by thermodynamic calculations, of a new 10%Cr martensitic steel for use at temperatures up to 620uC. The composition is designed to suppress Z phase formation, thus giving creep properties superior to those of steel 92.…”
Section: Parsons Turbine Conferencementioning
confidence: 99%